Assessment of some other traditional uses of accepted agroforestry fuelwood species in Akinyele and Ido local government areas, Oyo State, Nigeria (2010)
This study was carried out in order to assess some other traditional uses that some woody species can be put to, apart from their usefulness as fuelwood, using Akinyele and Ido Local Government Areas (LGAs), Oyo State, Nigeria, as a case study. Woody species found in agroforestry plots/farms in the study area, were compiled from questionnaires retrieved from 179 respondents, then prioritised using the respondents' ranking, from which twelve species that top the ranking were selected. Friedman chi-square result revealed that there was no statistically significant difference in the ranking pattern of the respondents in the two LGAs (x2=2.17; p<0.05). The questionnaire survey and literature search for other traditional uses to which the various parts of the accepted fuelwood species are put revealed that culinary and medicinal uses were dominant among these other uses. It was therefore recommended, based on this study, that management strategies that aim at balancing wood use as fuel and other traditional uses should be encouraged.